Henry Sweet stenografo e il ruolo della stenografia nella tradizione fonetica europea (Atti del Sodalizio Glottologico Milanese, 2019)
Starting from the wide recognition of Henry Sweet’s position among the highest representatives of European philology and phonetics in 19th-century linguistics, this paper aims to highlight the author’s specific interest in sound transcription as shown in the publication of A manual of current shorthand, orthographic and phonetic (1892). Far from representing a merely technical research unrelated to the phonetic investigations of the time, the shorthand tradition can be recognized to play a key role in linguistic analysis as it contributed to the introduction of the international phonetic alphabet. The purpose of this paper is to illustrate Sweet’s prominent position to connect the shorthand tradition in England and Europe to coeval scientific language studies. KEYWORDS: Henry Sweet, stenography, phonetics, history of linguistics, writing systems